THE COMPARATIVE ANALYSIS OF THE ULTRASONIC EXAMINATION AND Х-RAY MAMMOGRAPHY OF THE MEN WITH MASS PATHOLOGY IN THE MAMMARY GLAND PROJECTION - V. B. Akimova; D. V. Akimov (ABV-press, 2015)
Based on the scientific materials of domestic and foreign authors as well as on own observations, the results of the ultrasonic and mammographic research of the man's mass pathology in the mammary gland projection being found in the process of differential diagnosis between malignant and benign tumors with similar clinical picture are presented in the article. Methodologically there has been carried out the analysis of the distinctive and rare signs of the benign process and malignant transformation of the man's mass pathology in the mammary gland projection. In order to compare X-Ray and ultrasonic characteristics of the mass pathology in the patients' mammary gland projection similar visual effects in the process of the prebiopsy clinical diagnosis forming has been studied in pairs. Mammography pictures and visualization in B-regime have been studied critically: shape correctness, localization, irregularity and obscurity of contours, presence of pathological inclusions), data of the colour and spectral Doppler sonography and 3D-regime scanning. According to the results of visual examinaion objective indications for needle biopsy of the man's mass pathology in the mammary gland projection have been presented to the reader. The calculation of operation characteristics of different research methods of the mammary gland and combination of these methods has been done. The regularity of the information increase with an increase of the methods applied has been revealed. Based on the catamnesis examples of 317 men, the analysis of the necessity to make a combined examination variants of the mammary gland as the only definite opportunity to get a clinical diagnosis has been done.